An randomized controlled trial of Post‐it® notes did not increase postal response rates in older depressed participants - Lewis, Helen; Keding, Ada; Bosanquet, Katharine; Gilbody, Simon; Torgerson, David (Journal of evaluation in clinical practice, 2017)
Rationale, aims and objectives Our aim was to evaluate the effectiveness of a Post‐it® note to increase response rates and shorten response times to a 4‐month postal follow‐up questionnaire sent to participants taking part in the Collaborative Care in Screen‐Positive Elders (CASPER) trials. Method Our trial was a two‐arm randomized controlled trial comparing response rates to questionnaires with a printed Post‐it® note (intervention) and without (control), nested in multi centred randomized controlled trials of older people with varying levels of depressive symptoms; the CASPER+ and CASPER Self Help for those At Risk of Depression (SHARD) trials. A total of 611 participants were eligible and randomized. The primary outcome was response rates, secondary outcomes were time to response and need for a reminder. Results Of 297 participants, 266 (89.6%) returned their 4‐month questionnaire in the post‐it note arm, compared with 282 of 314 participants (89.8%) in the control arm (OR = 0.97, 95% CI: 0.57, 1.65, P = 0.913). There were no statistically significant differences in time to respond or the need to be sent a reminder. Patients with a major depressive episode were more likely to return questionnaires with post‐it notes (P of interaction = .019). Conclusion There was no significant difference in response rates, time to response, or the need for a reminder between the intervention and control at 4‐month follow up for older people with depressive symptoms. However, there was a significant interaction between the Post‐it® note group and level of depression.